Assessing the susceptibility of the selected gourami (Osphronemus goramy) to Aeromonas hydrophila - Rita Febrianti; Ikhsan Khasani; Keukeu Kaniawati Rosada (Smujo International, 2021)
Abstract. Febrianti R, Khasani I, Rosada KK. 2021. Assessing the susceptibility of the selected gourami (Osphronemus goramy) to Aeromonas hydrophila. Nusantara Bioscience 13: 111-120. A breeding program to improve the growth performance of the gourami fish was carried out through selection methods that produced faster growth gourami (selected population). The purpose of this study was to determine the susceptibility of the selected gourami to Aeromonas hydrophila infection based on tolerance limits (LD50) and investigated clinical signs post-injection of the pathogenic bacteria. The challenge test by intramuscular injection of A. hydrophila was done to the fingerling fish (15-20 g) for 14 days post-infection. The population of the tested fish was obtained from six families, selected gourami (SP), and non-selected control (CP) groups. Phosphate buffered saline (PBS) as control and several doses of the pathogen, 102, 104, 105, 106, 107, and 108 CFU/mL of A. hydrophila, were injected into the fish. Fish mortality and clinical signs were observed daily. The fish mortality was confirmed by isolating bacteria in the fish which showed clinical signs, followed by biochemical characterization of the isolated bacteria using API 20E and PCR. The LD50 of A. hydrophila to the selected population (9.70 × 105 CFU/mL) was higher than that of the control (6.50 × 104 CFU/mL). On the final day of the test, the accumulation mortality of CP (63.33±5.77%) higher than that in SP (33.33±5.77%). Based on the output test statistics, it was known that there was a significant difference between the mortality and clinical signs of SP and CP. The data suggested that the selected gourami were more resistant to A. hydrophila infection than that of the control. The A. hydrophila infection caused most of the major clinical signs, including mass mortality of the fish. The biochemical and PCR test ensure that fish mortality was caused by A. hydrophila infection.